Kritik Terhadap Pandangan Joel B. Green Mengenai Monism - Pieter Kurnia; Benyamin Intan (VERBUM CHRISTI JURNAL TEOLOGI REFORMED INJILI, 2021)
Green claims that monism is far more consistent than the separation of body and soul, also known as dualistic. Green said humans are whole humans and have no metaphysical aspects. All "metaphysical" aspects such as desire, will and every decision occur because of two things. First, there are chemical reactions in the brain or the result of neuroscience concepts and second, aspects of human relations. Green tries to prove this by using biblical texts and a word study approach. However, this view is problematic because it causes human identity to be lost when they die and become a new person when they are resurrected. Therefore, this article will evaluate Green's claims about monism. This evaluation will be reviewed and discussed from the Reformed point of view.